Molecular biophysics of strong DNA bending and the RecQ DNA helicase - Harrison, R (2014)
Molecular biophysics is a rapidly evolving field aimed at the physics-based investigation of the biomolecular processes that enable life. In this thesis, we explore two such processes: the thermodynamics of DNA bending, and the mechanism of the RecQ DNA helicase. A computational approach using a coarse-grained model of DNA is employed for the former; an experimental approach relying heavily on single-molecule fluorescence for the latter. There is much interest in understanding the physics of DNA bending, due to both its biological role in genome regulation and its relevance to nanotechnology. Small DNA bending fluctuations are well described by existing models; however, there is less consensus on what happens at larger bending fluctuations. A coarse-grained simulation is used to fully characterize the thermodynamics and mechanics of duplex DNA bending. We then use this newfound insight to harmonize experimental results between four distinct experimental systems: a 'molecular vise', DNA cyclization, DNA minicircles and a 'strained duplex'. We find that a specific structural defect present at large bending fluctuations, a 'kink', is responsible for the deviation from existing theory at lengths below about 80 base pairs. The RecQ DNA helicase is also of much biological and clinical interest, owing to its essential role in genome integrity via replication, recombination and repair. In humans, heritable defects in the RecQ helicases manifest clinically as premature aging and a greatly elevated cancer risk, in disorders such as Werner and Bloom syndromes. Unfortunately, the mechanism by which the RecQ helicase processes DNA remains poorly understood. Although several models have been proposed to describe the mechanics of helicases based on biochemical and structural data, ensemble experiments have been unable to address some of the more nuanced questions of helicase function. We prepare novel substrates to probe the mechanism of the RecQ helicase via single-molecule fluorescence, exploring DNA binding, translocation and unwinding. Using this insight, we propose a model for RecQ helicase activity.